PARTISIPASI DAN JAMINAN HAK POLITIK PENYANDANG DISABILITAS DI YAYASAN YUKARTUNI MAKASSAR PADA PEMILU LEGISLATIF 2014 - Zainal, Nur Aliyah; Iqbal, Muhammad Taufik (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
This article focuses on political participation and guarantee on political rights of disable voters during the 2014 legislative election in Makassar, particularly at Yukartuni Makassar Foundation, as well as focuses on some possible hindrances. The involvement of disable voters at Yukartuni Makassar Foundation is measurably significant during the election process in order to ease people with disability to deliver their electoral rights and to show their political participation. The assurance towards political rights of disable voters at Yukartuni Makassar has been met, which can be identified during the 2014 legislative election. They have been involved during the campaign period, not only during the visit of the candidates to the Foundation to deliver the latter’s vision, mission and programs, but also attending the candidates’ campaign process at the other places by showing their talents of singing, for instance. Some hindrances apparently emerged during the election period, since they voted for certain candidates due to money politics, or being unable to vote for having no Makassar identity cards. Some other difficulties may be listed during the Election Day such as the illiterate of some disable voters towards braille ballots, the insufficiency of braille ballots and the disable voters’ arrival at the voting place without someone to accompany and to assist them.